2010
DOI: 10.1111/j.1471-0528.2010.02779.x
|View full text |Cite
|
Sign up to set email alerts
|

The surgical transversus abdominis plane block-a novel approach for performing an established technique

Abstract: Although the transversus abdominis plane (TAP) block has an established role in providing postoperative analgesia following caesarean section, the technique is not widely used by obstetric anaesthetists. The conventional TAP block is associated with significant technical difficulties and risk of peritoneal, hollow viscus and organ perforation. We report a much simpler technique in which the obstetric surgeon, during open surgery, is able to introduce the TAP block via an intra-abdominal approach, which is tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 6 publications
2
36
0
1
Order By: Relevance
“…In year 2011, Owen et al [5] described a new approach: TAP block under direct vision in open surgery they concluded that the risks associated with the conventional approach could be prevented with this easy technique. In the same year, Magee et al [6], reported a single case based on the same idea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In year 2011, Owen et al [5] described a new approach: TAP block under direct vision in open surgery they concluded that the risks associated with the conventional approach could be prevented with this easy technique. In the same year, Magee et al [6], reported a single case based on the same idea.…”
Section: Discussionmentioning
confidence: 99%
“…So far, transversus abdominis plane (TAP) block technique which was first reported by Rafi [4], seems to offer an effective local pain control to the patients. Owen et al [5] first described the open surgical approach for TAP block. A few years later, in 2011, pure laparoscopic TAP block was reported as a new technique [6].…”
Section: Introductionmentioning
confidence: 99%
“…53 An alternative technique has been described in open abdominal surgery, where the wound edges are retracted and a needle inserted from the interior of the abdomen through the parietal peritoneum and into the TAP as signaled by a single tactile pop. [54][55][56] Finally, a technique of surgical dissection into the TAP, followed by direct injection or placement of a catheter, has been described in abdominoplasty 57 and abdominal flap breast reconstruction surgery. 58 Advantages cited for the surgical approach include better matching of the site of injection to site of surgery, ease and speed of performance, and accuracy of injection into the correct tissue plane.…”
Section: Surgical Tap Blockmentioning
confidence: 99%
“…More recently, a surgical TAP block utilizing a transperitoneal approach was also described. Performed intraoperatively, a blunt-tipped block needle was advanced from inside the abdominal wall through the parietal peritoneum, then the transversus abdominis muscle, and into the TAP as indicated by a single pop sensation [17, 18]. In addition, Araco et al described a surgical TAP block in which blunt dissection through the external and internal oblique muscles leads to injection of local anesthetic into the TAP under direct visualization [19].…”
Section: Techniquementioning
confidence: 99%